A New Look at the Neural Diathesis–Stress Model of Schizophrenia: The Primacy of Social-Evaluative and Uncontrollable Situations - Jones, Simon R. (Oxford University Press, 2007)
The neural diathesis–stress model of schizophrenia proposes that stress, through its effects on cortisol production, acts upon a preexisting vulnerability to trigger and/or worsen the symptoms of schizophrenia. In line with its focus on the neurobiology of stress response in schizophrenia, this model treats stressors as a homogeneous category. Recent research has shown that, in healthy individuals, cortisol is most strongly produced in response to stressors that result from perceived uncontrollable threats to important goals and/or social-evaluative threats. We hypothesize that it is specifically these stressors that trigger and/or worsen the symptoms of schizophrenia in those with a preexisting vulnerability. This hypothesis may provide a way of making sense of contradictory findings on the relations between stress and schizophrenia. We propose some empirical tests of this hypothesis and explore implications for the treatment and management of the disorder.